Raw material base of Russia’s unconventional oil and gas reserves (hydrocarbons shale strata) - Prischepa, Oleg; Nefedov, Yuri; Nikiforova, Victoria; Ruiming, Xu (Frontiers in Earth Science, 2022)
One of the most controversial and discussed issues related to the development of the hydrocarbon raw material base in recent years is the issue of exploring the possibilities of involvement in industrial development accumulations associated with high-carbon shale complexes that are widespread in Russia. Interest therein is supported by the system of benefits provided by the Government for low-permeability reservoirs and special preferential conditions for geological exploration provided to subsurface users in recent years. An important effect was also achieved by developing a methodology for reserves assessment and placing on the state balance a whole series of fields with oil deposits in the Domanik formation of the Volga-Ural oil and gas province (OGP). Simultaneously, the assessment of the potential of high-carbon formations in the Russian Federation mainly continues to be the subject of scientific research without an applied component, due to its inapplicability for selecting both the most significant areas for exploration and the possibilities of using it to justify investments. Here, the uncertainty is related to the estimation of possible production levels with an unclear correlation between development technologies, filtration and reservoir properties, and the potential of high-carbon strata. This study discusses two approaches that allow assessment of the potential of the main high-carbon strata distributed in Russia.